Long-term gastrointestinal adverse effects of doxycycline - Khalid Eljaaly; Haifa Alghamdi; Hadeel Almehmadi; Fahad Aljawi; Ammar Hassan; Abrar K Thabit (Journal of Infection in Developing Countries)
Introduction: Doxycycline is an antibiotic with known gastrointestinal (GI) adverse effects. Esophagitis is the most pronounced among these effects, and might be associated with a prolonged duration of therapy. The aim of this study is to evaluate the incidence of esophagitis and other GI side effects in adults who received doxycycline for at least a month.